Paget's disease of the breast in men: Clinical case. Literature review - Palacio, José Luis; Llorens, Ricardo; Ituño, Carlos (Cirugía del Uruguay, 1994)
A case of Paget's sease of the breas/ in males is presented; clinical presenta/ion consisted of the presence of a palpable tumor associated to nipple and areola eczema. lt is an infrequent case, which can de/ay diagnosis and eatment. The clinical and histological aspects of this rare tumor are analysed and a review of cases published in intenational literature is made